PENGARUH PENGGUNAAN MEDIA WAYANG KERTAS TERHADAP KEMAMPUAN MENYIMAK ANAK USIA DINI PADA KELOMPOK A RA BAITUSSALAM BANDUNG - Tasya Salsabila Gumanti; Ida Rosyidah; Zaenal Muftie (JIP: Jurnal Ilmu Pendidikan, 2025)
This research is based on the idea that children's listening ability is the initial and basic thing in children's language skills before they can speak, read and write. It is motivated by the underdevelopment of children's listening skills, evidenced when the learning process takes place the child is still less focused, so that it has an impact on the child's lack of understanding of the material presented. This study aims to determine children's listening skills through paper puppet media (Experimental Group), listening skills through picture book media (Control Group), the effect of using paper puppet media on children's listening skills. The method used in this research is quantitative using a quasi-experimental approach. Data collection techniques in the form of observation. Data analysis using normality test, homogeneity test, hypothesis test (t test). The results showed that there was an effect of using paper puppet media on children's listening skills. This can be seen from the average value of the experimental group which was originally 55.8 to 81.3 with very good interpretation. While in the control group the average value of the pretest was 50.7 and the posttest was 65.3 with the interpretation of the sufficient category. The results of the analysis calculation of the hypothesis test tcount = 2.403> ttable = 2.228 at a significant level of 5%. So it can be concluded that Ho is rejected and Ha is accepted. So there is an effect of using paper puppet media on children's listening skills.